Danish association football coaches` perception of performance analysis - Andersen, L. W.; Francis, J. W.; Bateman, M. (International Journal of Performance Analysis in Sport, 2022)
Performance analysis (PA) has become a key requirement for association football coaches within England to aid their practice but less is known in other countries. We examined the perceptions of Danish association football coaches towards the use and engagement with PA. An online survey with 34 open-ended and close-ended questions was completed by 200 UEFA A and Pro Licenced coaches, gaining insights into how the coaches` engaged with PA, how PA supported their practice and the future of PA in Denmark. Additionally, five male coaches completed a semi-structured interview. UEFA Pro Licenced coaches had greater experience with analysis support and perceived the importance of video for opposition and reviewing their own team`s performance with higher regard than UEFA A Licenced coaches. Cost and time were highlighted as barriers, but a clear desire to have a dedicated performance analyst was acknowledged by all coaches. The research findings provide key considerations regarding the knowledge and understanding of how Danish football coaches review and evaluate performances, highlight the perceived benefits of PA and acknowledge a desire to increase investment. The insights can be used to inform future decision making regarding the direction of PA provision and the education and development of Danish coaches.